Nepalese Medical Students’ Perception of Human Cadavers: Ethical Perspectives (Nepal Journal of Health Sciences, 2025)
Introduction: Cadaveric dissection has long been a cornerstone of medical education. In Nepal, medical students are introduced to cadavers through demonstrations that serve as an essential method for teaching and learning anatomy. Understanding how students perceive the dead body and its dissection is crucial to fostering a respectful learning environment and reinforcing ethical conduct.Objective: This study aims to study medical students’ perceptions of cadavers and to discuss its ethical aspects.Methods: This descriptive cross-sectional study was conducted in Devdaha Medical College through convenient sampling of 160 preclinical medical students. Structured questionnaires were used to collect data, which were kept anonymous. They were entered in Microsoft Excel and the results were expressed in frequency and percentage.Results: Most students felt intense emotions (36.7%), exposed to death (61.5%), and found it to be a transformative experience (75.2%) after dealing with a cadaver. Majority of them agreed to have been considerate towards cadavers (88.1%), contemplate morality (91.7%), respectful (73.4%) and follow the code of conduct (88.1). Maximum students perceived cadaver to be essential to medical education (90%) and obligation to learn (82.6%), while a slightly more (40.4%) disagreed to be desensitize to the emotional and cognitive difficulties.Conclusion: Medical students largely perceive cadavers positively and as learning tools, enabling them to approach dissection with objectivity while fostering a sense of detached concern.